Kegiatan Permainan Edukatif Interaktif Melalui Gerakan Cinta Sastra Sejak Dini Bagi Siswa SD Majasari - Revalita Bintang Permana Putri; Yully Yuliani Wartini; Vina Marliyana; Nia Sari; Desti Kusmayanti; Firmansyah (Pusmedia Group Indonesia, 2026)
Literary literacy education at the elementary level often faces stagnation due to rigid and teacher-centered instructional methods, as observed at SD Majasari, Subang Regency. Limited teaching media caused 75% of 5th-grade students to be passive, easily bored, and experience language anxiety. This community service activity aimed to transform the atmosphere of literary learning into an interactive and student-centered environment through the implementation of sequential educational games. The implementation method utilized Participatory Action Research (PAR), encompassing cycles of planning, acting, observing, and reflecting. The participants consisted of 24 fifth-grade students of SD Majasari (aged 10–11 years). The intervention was conducted through the simulation of three thematic literary games, namely “Estafet Kata Ajaib” (receptive aspect), “Detektif Puisi” (paralinguistic expressive aspect), and “Tebak Gambar Jadi Cerita” (collective creativity), integrated with a positive reinforcement system. Evaluation data were collected through participant observation, documentation, and product analysis, which were then analyzed descriptively and qualitatively. The results demonstrated a significant increase in students' active participation, public speaking confidence, listening acuity, and theatrical expression. Furthermore, the program successfully stimulated group creativity, producing a coherent collective short story draft. The implication of this activity proves that an adaptive game-based learning approach can mitigate children's psychological-linguistic barriers and reconstruct elementary classrooms into an inclusive and joyful literacy ecosystem.